Declining orangutan populations in and around Danau Sentarum - Russon, A.E.; Meijard, E.; Dennis, R.A. (2000)
This paper presents the combined results of two separate orangutan survey efforts and an assessment of land cover change analysis in the Danau Sentarum, National Park (DNSP), West Kalimantan, Indonesia These studies show that the DNSP and surrounding areas contain high numbers of orangutans, making these populations of global significance to the species survival in the wild. However, in the park and its surrounding areas, 40,339 ha habitat disappeared between 1973 and 1990, and 32,586 ha between 1990 and 1997. This equals a total decrease of 29% in the total orangutan habitat over the past 27 years. In that same period contigious habitat patches judged to be large enough to support a substantial orangutan population also decreases in number and in size. Therefore, orangutan populations in DNSP are likely in decline. In addition to this the most recent land cover changes and land-use plans indicate that much primary orangutan habitat is still targeted for logging or conversion into plantations. The main reason for decreasing trend in orangutan population is that the present Park boundary does not include the most important contigious orang utan habitats in the north and east of the park. Therefore it is recommended extending the boundary of the present park to include prime unprotected orangutan habitat. Also, connecting the Park to the nearby Bentuang Karimun National Park would joint two important, now segregated orangutan population and therefore improve the long-term survival prospects for the species in this region.